Assessment of working Conditions and Physical Fitness of Female Tobacco Workers in Different Tobacco Units at Jaisingpur City of Kolhapur District Maharashtra - B S, Wali (International Journal of Pharmaceutical & Biological Archive, 2013)
Assessment of working Conditions and Physical Fitness of Female Tobacco Workers in Different Tobacco Units at Jaisingpur City of Kolhapur District Maharashtra